Digital Transformation - Challenges Faced by SME ICT Service Providers - Gogulakrishnan, Karthika (Digital Repository of Theses - SSBM Geneva, 2024)
Organizations need to adopt digital transformation to sustain themselves in the market. The current pandemic situation is also forcing all organizations, big and small, to embrace digital transformation. SME ICT service providers help their customers in digital transformation. They face challenges in their transformation because digital transformation is more than merely implementing new tools and technology. It is the process of adopting new technologies to modify or create new business processes, customer experience and culture to meet the evolving needs of the business. This paper will study SME ICT service providers' challenges in adopting digital transformation and address the gaps. The proposed study will use both qualitative and quantitative methods for data collection and focus more on the processes and people-related factors imperative for Digital transformation. The study analyzes various frameworks, models and approaches for SME ICT service providers for digital transformation using the literature review. Linear regression and Pearson co-efficient was done using the survey data to find the relationship between the drivers and barriers. Both positive and negative relationships were found using survey data. Drivers and barriers that are found to be related to each other are found to be people and process-centric characteristics. This study encourages further research on the same problem in a different setting or context.